The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/1983-084x/11_187
|View full text |Cite
|
Sign up to set email alerts
|

Teor e composição do óleo essencial de patchouli (Pogostemon cablin (Blanco) Benth.) após diferentes tempos de secagem em estufa e temperatura ambiente

Abstract: RESUMO:Patchouli é uma espécie aromática pertencente à família Lamiaceae que possui óleo essencial com alto valor comercial devido à aplicação nas indústrias de higiene, cosméticos e perfumarias. Considerando as características voláteis e estruturas de armazenamento em diferentes órgãos das plantas aromáticas, a determinação de métodos de secagem é de extrema importância e pode afetar tanto o rendimento como a composição do óleo essencial. Este trabalho teve como objetivo principal avaliar o teor e a composiçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Considering the storage structures found in different organs and the volatile constituents of the aromatic plants, the selection of the appropriate drying methods is important because drying can affect the yield and the chemical composition of the essential oil [35,48]. We did not find previous studies evaluating the effect of different drying conditions on the yield of essential oil of L. thymoides, however, Ebadi et al (2015) [49] investigated the drying of Lippia citriodora leaves using different methodologies including oven-drying (40, 50, and 60 • C), and they found that the increase in temperature generated damage to glandular trichomes, which may have favored the loss of volatiles and the reduction in the yield [49].…”
Section: Drying Effects On Essential Oil Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the storage structures found in different organs and the volatile constituents of the aromatic plants, the selection of the appropriate drying methods is important because drying can affect the yield and the chemical composition of the essential oil [35,48]. We did not find previous studies evaluating the effect of different drying conditions on the yield of essential oil of L. thymoides, however, Ebadi et al (2015) [49] investigated the drying of Lippia citriodora leaves using different methodologies including oven-drying (40, 50, and 60 • C), and they found that the increase in temperature generated damage to glandular trichomes, which may have favored the loss of volatiles and the reduction in the yield [49].…”
Section: Drying Effects On Essential Oil Yieldmentioning
confidence: 99%
“…However, drying can cause changes in the yield of essential oils, polyphenols, pigments, and vitamin contents as well as appearance, taste, and color [32]. Different drying techniques have been applied to various aromatic plants to evaluate the effect of drying on the color, composition, and yield of the essential oils as well as to determine the best method for drying a specific plant [33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…A species rich in essential oils is patchouli (Pogostemon cablin), an aromatic plant belonging to the Lamiaceae family whose oil extracted from its leaves is widely used as an important raw material in the manufacture of soaps, incense, cosmetics, and oral hygiene products. This oil is known for its antibacterial, insecticidal, antioxidant, repellent, and anti-adherent activities [18]- [20].…”
Section: Introductionmentioning
confidence: 99%